2000
DOI: 10.1002/(sici)1096-8628(20000228)90:5<423::aid-ajmg12>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Holoprosencephaly, hypertelorism, and ectrodactyly in a boy with an apparently balanced de novo t(2;4)(q14.2;q35)

Abstract: A holoprosencephaly, hypertelorism, and ectrodactyly syndrome (HHES) was described in three previous cases in whom chromosomes were apparently normal. We report on a 3-year-old boy with HHES and a de novo apparently balanced t(2;4)(q14.2;q35) confirmed by fluorescent in situ hybridization. He had severe growth and mental retardation, lobar holoprosencephaly, hypertelorism, microphthalmos, and iris, choroid, and retina colobomata. Less-severe facial involvement correlates with the semilobar type of holoprosence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…An apparently balanced de novo translocation with a breakpoint at 2q14.2 was identified in a patient with SHFM and holoprosencephaly (HPE) [Corona-Rivera et al, 2000]. A patient with SHFLD was later found to have a balanced translocation that also involved 2q14.2 [Babbs et al, 2007].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…An apparently balanced de novo translocation with a breakpoint at 2q14.2 was identified in a patient with SHFM and holoprosencephaly (HPE) [Corona-Rivera et al, 2000]. A patient with SHFLD was later found to have a balanced translocation that also involved 2q14.2 [Babbs et al, 2007].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…8 Comparative mapping of the two chromosomes 2 breakpoints BAC clones were selected on the basis of the cytogenetically established chromosome breakpoint regions ( Figure 2a and b) using the ensemble database. These were hybridized against metaphase chromosome spreads of the two probands.…”
Section: Probands and Cytogenetic Analysismentioning
confidence: 99%
“…As an example, a holoprosencephaly, hypertelorism and ectrodactyly syndrome (HHES), considered as an independent clinical entity, was reported to be associated with an apparently balanced de novo translocation [t(2;4) (q14.2;q35)] in a Mexican patient. 8 In addition to this case, an association of ectrodactyly with holoprosencephaly has been reported in six additional probands (reviewed by König et al 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, two pieces of evidence suggested that the 2q14.2 breakpoint might signal a locus for SHFLD. First, the report of a patient with a t(2;4)(q14.2;q35) translocation associated with holoprosencephaly and ectrodactyly suggested a common aetiology (Corona-Rivera et al 2000). Second, deletions of the short arm of chromosome 18 are relatively frequent and are not associated with limb abnormalities while conWrmed deletions of 2q14.2 are extremely rare (Schinzel 2001).…”
Section: Introductionmentioning
confidence: 64%